Instagram, Pandemi, dan Peran Influencer (Analisis Wacana Kritis pada Postingan Akun Instagram @najwashihab dan @jrxsid) - Achmad Zuhri (Academic Journal of Da'wa and Communication, 2020)
The spread of information relates to Covid-19 on social media increasingly widespread causes the government to use persuasive communication patterns. However, the communication strategiesÂ carried out by the government through influencers do not fully receive support. The Instagram accounts of @najwashihab and @jrxsid are interesting to study because they have such a wide influence on the way the public views this pandemic. The construction of discourse developed by their Instagram content was analyzed. This study used critical discourse analysis method of text and documentation as well as content display analysis. It is found that these accounts have a variety of views in understanding the Covid-19 phenomenon. Through textual analysis, social cognition, and social concepts initiated by Teun Van Dijk, these accounts incorporate the cognitive abilities in their posts. The @najwashihab account is much more acceptable than @jrxsid because its argument is in line with the narrative developed by the government. The language style used by @jrxsid shows a critical attitude towards policies that are pro to WHO. However, @jrxsidreceives more provocative comments from the followers than the @najwashihab account. In the same way, these accounts have similarities in their concern for the people affected by Covid-19. Both accounts have creativity in displaying content with an attractive visual style and have social responsibility.